Steroid Psychosis: A Case Series of Three Patients - Menon, Vineetha Bharathan; Sunny, Ansu Anie; Pereira, Pratibha; Chikkaveeraiah, Shashidhara; Ramesh, Madhan (Indian Journal of Pharmacy Practice)
Background: Steroids are widely used in modern medicine for the treatment of various ailments. Steroid psychosis is a known complication of steroid therapy, although infrequent. Herein we describe a series of three cases where patients presented with pure psychosis without mood disturbance, which is highly unlikely, following steroid therapy. Cases: Two female and one male patients aged 23 years, 50 years and 80 years respectively developed psychosis following steroid administration. In the first case, oral methylprednisolone (48 mg/day) was used in the management of systemic lupus erythematosus, second case received intravenous dexamethasone (36 mg/day) for the management of bronchopneumonia, while third case had a two day course of intravenous methylprednisolone (120 mg/day) for the treatment of chronic obstructive pulmonary disease. Conclusion: Consistent with the previous studies, female gender and high steroid dose were identified as the common risk factors for the development of steroid psychosis. Steroid psychosis is a major complication, which if recognized early can be effectively treated. Treatment with high dose of steroids should be used cautiously to avoid psychotic adverse reactions.
Keywords: Adverse drug reaction; Case series; Corticosteroids; Psychosis.